Sucrose reduction with maintained sweetness level lowers glycemic fluctuations and energy intake in healthy males - Gaider, Marlies; Kimmeswenger, Isabella; Schmidt, Jana; Thines, Cynthia; Wu, Anni; Stoffl, Teresa K.; Rust, Petra; Ley, Jakob P.; Krammer, Gerhard E.; Somoza, Veronika; Lieder, Barbara (Frontiers in Nutrition, 2025)
IntroductionThe sole perception of sweet taste is discussed to interfere with postprandial blood glucose regulation and leading to enhanced cravings for sweet foods. This raises the question whether preserving sweetness while reducing sugar in a test solution can sustain beneficial effects on blood glucose regulation and subsequently decrease postprandial energy intake. Specifically, we hypothesized that reducing the caloric load of a sucrose solution while maintaining the perceived sweetness intensity by adding hesperetin as a taste modifier attenuates large fluctuations in postprandial blood glucose concentrations with beneficial effects on appetite and cravings for sweet foods.MethodsIn a randomized crossover study with 32 healthy male participants, the effect of a 10% sucrose solution on blood glucose regulation and energy intake was compared to an equi-sweet 7% sucrose solution with 50 mg/L hesperetin. Data was analyzed using paired Student’s t-tests or Repeated-measures ANOVA. The study was approved by the ethical committee of the University of Vienna (approval number 00903) and registered at ClinicalTrials.gov (NCT05705596).ResultsThe results show that the decline in blood glucose concentrations was less pronounced after consumption of the 7% sucrose solution with hesperetin than after the isosweet 10% sucrose solution. Additionally, participants reported less desire for a sweet snack and had on average a 10 ± 7% (p < 0.05) lower energy intake after consumption of the 7% sucrose hesperetin-spiked solution.ConclusionIn conclusion, our results argue for a pronounced role of the carbohydrate content in postprandial appetite regulation.